The political languages of emancipation in the British Caribbean and the U.S. South - Eudell, Demetrius Lynn (The University of North Carolina Press, 2002)
An examination of the emancipation process in the British Caribbean, particularly Jamaica, during the 1830s, and in the USA, particularly South Carolina, during the 1860s. It explores how former slaves, former slaveholders, and their governments understood and discussed slavery and emancipation.